Update of the European consensus on sarcopenia: what has changed in diagnosis and prevalence in peritoneal dialysis? - da Silva, Maryanne Zilli Canedo [UNESP]; Vogt, Barbara Perez; Reis, Nayrana Soares do Carmo [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP] (Springer Nature, 2019)
Patients on peritoneal dialysis (PD) may be affected by sarcopenia, which is a progressive and generalized skeletal muscle disorder characterized by muscle mass atrophy with decline of muscle strength and function. The aim was to evaluate differences in the diagnosis and prevalence of sarcopenia according to European Working Group on Sarcopenia in Older People (EWGSOP). The screening for sarcopenia was performed in PD patients older than 18 years, with evaluation of appendicular skeletal muscle mass index (ASMMI), handgrip strength (HGS) and gait speed (GS). The diagnosis was according to the 2010 and 2019 versions of EWGSOP consensus on sarcopenia. Fifty subjects on PD were included, mean age 55.74 ± 16.22 years old, 52% female. The prevalence of sarcopenia ranged from 4 to 10% according to cut points and references used.